2011
DOI: 10.1038/gt.2011.201
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus B3 used as a gene therapy vector to express functional FGF2

Abstract: Current gene therapies are predominantly based on a handful of viral vectors. The limited choice of delivery vectors has been one of the stumbling blocks to the advancement of gene therapy. Therefore, the development of novel recombinant vectors should facilitate the application of gene therapies. In this study, we examined coxsackievirus B3 (CVB3) as a novel recombinant vector for the delivery and expression of a foreign gene in vitro and in vivo. A recombinant CVB3 complementary DNA was constructed by insert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Many of these recombinant viral constructs have proven to be quite stable, although the loss of the foreign insert can appear in the viral population within five passages, depending upon the size of the insert, nucleotide sequence, nature of the gene, and passage conditions. The utilization of these rCVBs in tissue culture and in vivo have clarified questions regarding viral tropism (Feuer, Pagarigan et al, 2005) (Puccini, Ruller et al, 2014), activation of the adaptive immune response against infection (Kemball, Harkins et al, 2009), mechanisms of virulence and disease (Zeng, Chen et al, 2013), and possible uses of CVB as therapeutic/vaccine vectors (Kim, Kim et al, 2012) (Miller, Geng et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Many of these recombinant viral constructs have proven to be quite stable, although the loss of the foreign insert can appear in the viral population within five passages, depending upon the size of the insert, nucleotide sequence, nature of the gene, and passage conditions. The utilization of these rCVBs in tissue culture and in vivo have clarified questions regarding viral tropism (Feuer, Pagarigan et al, 2005) (Puccini, Ruller et al, 2014), activation of the adaptive immune response against infection (Kemball, Harkins et al, 2009), mechanisms of virulence and disease (Zeng, Chen et al, 2013), and possible uses of CVB as therapeutic/vaccine vectors (Kim, Kim et al, 2012) (Miller, Geng et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Within this context, both CVB3 and CVA21 have proven useful for gene therapy and vaccine development ( Lundstrom, 2023 ; Bradley et al, 2014 ). In particular, recombinant CVB3 expressing the human fibroblast growth factor 2 (FGF2) demonstrated protection against ischemic necrosis after administration into mice with ischemic hindlimbs ( Kim et al, 2012 ). Additionally, it has been shown that recombinant CVB3 expressing IFN- γ is an important approach for preventing CVB3-induced myocarditis and for providing long-term immune response ( Henke et al, 2008 ).…”
Section: Coxsackieviruses As a Viral Vector System For Gene Therapy A...mentioning
confidence: 99%
“…Coxsackieviruses have been used for several gene therapy applications [ 23 ]. For instance, the coxsackievirus B3 (CVB3) expressing the human fibroblast growth factor 2 (FGF2) was injected into ischemic hindlimbs of mice showing protection from ischemic necrosis [ 76 ]. The treatment improved the blood flow in ischemic limbs for more than 3 weeks.…”
Section: Viral Vectorsmentioning
confidence: 99%